2022
DOI: 10.1186/s12940-022-00889-1
|View full text |Cite
|
Sign up to set email alerts
|

Ambient air pollution and thyroid function in Spanish adults. A nationwide population-based study (Di@bet.es study)

Abstract: Background Recent reports have suggested that air pollution may impact thyroid function, although the evidence is still scarce and inconclusive. In this study we evaluated the association of exposure to air pollutants to thyroid function parameters in a nationwide sample representative of the adult population of Spain. Methods The Di@bet.es study is a national, cross-sectional, population-based survey which was conducted in 2008-2010 using a random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The findings in newborns/infants are, however, in agreement with the data collected in adults, as shown in the Di@bet.es study ( 35 ), where a significant negative association between exposures to PM 2.5 and thyroid hormone levels was described, moreover, with relatively low PM 2.5 concentration ranges, well below the existing European Ambient Air Quality Directive target values (PM 2.5 <25 µg/m 3 ) ( 20 ). To date, the WHO guidelines recommend a maximum annual PM 2.5 exposure < 5 µg/m 3 ( 16 ).…”
Section: Effects Of Environmental Pollutants On Thyroid Function and ...supporting
confidence: 88%
“…The findings in newborns/infants are, however, in agreement with the data collected in adults, as shown in the Di@bet.es study ( 35 ), where a significant negative association between exposures to PM 2.5 and thyroid hormone levels was described, moreover, with relatively low PM 2.5 concentration ranges, well below the existing European Ambient Air Quality Directive target values (PM 2.5 <25 µg/m 3 ) ( 20 ). To date, the WHO guidelines recommend a maximum annual PM 2.5 exposure < 5 µg/m 3 ( 16 ).…”
Section: Effects Of Environmental Pollutants On Thyroid Function and ...supporting
confidence: 88%
“…11−13 Epide-miological studies have also shown associations between environmental factors (e.g., air pollution) and changes in the HPT axis. 14 These results require a better understanding of the environmental etiology of TH dysfunction to inform preventive strategies. Unfortunately, there is no human evidence to date on which and how far pollutants would disturb peripheral TH metabolism beyond deiodination, largely due to the lack of sensitive markers to indicate metabolic variations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Increasing numbers of environmental chemicals have been suggested as thyroid disruptors . Animal studies with large doses of exposure have revealed significant changes in circulating TH levels partially via interference with the HPT axis and iodine-centered peripheral metabolism. Epidemiological studies have also shown associations between environmental factors (e.g., air pollution) and changes in the HPT axis . These results require a better understanding of the environmental etiology of TH dysfunction to inform preventive strategies.…”
Section: Introductionmentioning
confidence: 99%